Intertextual observations of Jimmy Boyle’s handwritten manuscripts - Chan, Cheong Jan; Kwan, Chiou Yueh; Lee, Sze May; Boyle, James P. S. (Universiti Pendidikan Sultan Idris, 2020)
Our study on Jimmy Boyle (1922-1971) has been one that attempts to unfold the many facets of his creativity against the single-dimensional image of a patriotic songwriter. His sentiments as songwriters of many kind, a jazzman, and a cultural enthusiast have been proven through his different branches of work that are at times seem contrasting with each other in compositional styles. As a result of a long term archiving project, this paper reveals the entire set of handwritten artefact left after his death in 1971 and was recovered in Universiti Putra Malaysia in 2014, namely some 177 items of Boyle’s handwritten manuscript, that contains unpublished, published compositions as well as hand copy of others’ compositions. Main methods employed were that of the construct of taxonomy, and some cross-examination of the items covered within the catalogue mooted by the concept of intertextuality. Through narrating the interlinks between multiple manuscripts surrounding ‘Mutiara Ku’, ‘Pulau Pinang’ and ‘Medhini’, the process of composition was brought to life in displaying the all rounded capacity of Boyle.